Challenges of Handling Bulk Cargoes at Discharging Port - S. Vasantha (International Journal of Supply Chain Management, 2018)
Abstract-This study is based on bulk cargo handling by a freight forwarding company. Due to heavy globalization, the number of companies operating overseas is continuously extending their organizations offering the capability to deal with the complexities inherent in international trade. Since bulk cargo handling plays a wise role in the logistics industry are considered as main logistic mediator in trade, selecting a freight forwarder is a significant element in a company's success overseas. As major challenges are faced while handling bulk cargoes which has to be tackled as early as possible for future development. The study attempts to analyse the issues in handling bulk cargoes and techniques used for handling bulk cargoes which would help to resolve issues and contributes for major improvement for loading and unloading. There are different storage methods and the different types of bulk cargoes are stored differently and different handling equipments are used. The study is based on both primary and secondary data. The primary data is collected from 50 respondents through questionnaire survey. Keywords: Bulk cargo, Effectiveness, port, safety